The characteristics of Muslim celebrities endorsers and its influence on consumers' purchase intention - Marliza Zulaikha binti Mohamad Noor (Kulliyyah of Economics and Maangement Science, International Islamic University Malaysia, 2016)
This study was conducted to identify the Muslim Celebrity endorser's characteristics influence on consumers' purchase intention in Malaysia. The study is based on a sample of 231 respondents in Kelantan. The data was analyzed using statistical package for social sciences (SPSS) version 19 which include descriptive analysis, correlation, and multiple regression analysis. The results show that there are significant relationships between expertise, trustworthiness, and ethical values with the purchase intention. Among the three characteristics, expertise is the one that influence the consumers' purchase intention the most, followed by ethical value and trustworthiness. Surprisingly, the attractiveness of the Muslim celebrities endorsers is found to be not significant to the consumers' purchase intention. Therefore, managers need to consider Muslim celebrities with relevant characteristics to represent their products or brands.